Motivating students / edited Sally Brown, Steve Armastrong, Gail Thompson. - Brown, Sally; Armstrong, Steve; Thompson, Gail. (London : Kogan page., 1998)
This work brings together the experience of educators, trainers and students searching for ways of increasing student motivation. Links between motivation and training, learning and assessment processes are examined through case studies set in a broad range of subject discipline contexts.
Includes reference and index.
Keywords: Motivation in education; College students; Psychology